Succeed in ielts listening and vocabulary : - Betsis, Andrew (Tổng hợp, 2014)
It contains in-depth strategies for developing students' listening skills. All the different tasks of the IELTS Listening section, such as maps, iagrams, flowcharts, multiple-choice, gap filling, true-false, matching etc. are included